Developments in international banking since 1973 - Wijnholds, J.A.H. de Beaufort (Amsterdam : De Nederlandssche Bank N.V., 1978)
The international operations of the international banks, and more in particular the so-called Eurobanks, have shown a continued vigorous expansion over the past four years. These are discussed here mainly from the monetary point of view.
This article was published in: De Nederlndsche Bank N.V., Quarterly Statistics, no.2 September 1978, pp. 84-94
osc 12/05/2017
Loans
Keywords: International banks